THE RELATIONSHIP OF STUDENT PARTICIPATION IN IMPROVING STUDENT ACHIEVEMENT IN SMP NEGERI 1 X KOTO ABOVE - Puja May Yassha; Yesasri Yesasri; Merika Setiawati (Sean Institute, 2022)
This research was motivated by the lack of student participation in learning social sciences. The objectives of this study were (1) to find out whether there was a relationship between student participation in improving student achievement in class VIII SMP Negeri 1X Koto Above. (2) knowing the magnitude of the relationship between participation in improving student achievement in class VIIISMP Negeri 1 X Koto Above. Data collection technique using questionnaires and data analysis techniques using product moment correlation technique. The results of this study are that there is a positive and significant relationship between student participation in improving student achievement in class VIII SMPN Negeri 1 X Koto Above. This is evidenced from the result of the analysis obtained that rcount = 0,537 is greater than rtable (sig. 5% for N = 37) which is 0,31 and the correlation test result is 0,4 it is stated that the relationship between participation and achievement variables is quite strong.Keywords: Participation, Achievement, And Students.